Antitumor activity of the multikinase inhibitor regorafenib in patient-derived xenograft models of gastric cancer - Huynh, Hung (J Exp Clin Cancer Res, 2015)
BACKGROUND: Unresectable gastric cancer is associated with poor outcomes, with few treatment options available after failure of cytotoxic chemotherapy. Clinical trials of targeted therapies have generally shown no survival benefit in gastric cancer, with the exceptions of the antibodies ramucirumab (anti-VEGFR2) and trastuzumab (anti-HER2/neu). Given the efficacy of the multikinase inhibitor regorafenib in other gastrointestinal tumors, we investigated its potential in gastric cancer. METHODS: The antitumor activity of oral regorafenib was assessed in eight murine patient-derived gastric cancer xenograft models. Dose–response experiments assessed the efficacy and tolerability of oral regorafenib 5, 10, and 15 mg/kg/day in two models, with 10 mg/kg/day selected for further investigation in all eight models. Tumor weight and volume was monitored during treatment; tumor cell proliferation, angiogenesis, apoptosis, and intracellular signaling were assessed using immunohistochemistry and Western blotting of total tumor lysates at the end of treatment. RESULTS: Regorafenib showed dose-dependent inhibition of tumor growth and was well tolerated, with no significant decreases in bodyweight or evident toxicity. Regorafenib 10 mg/kg/day significantly inhibited tumor growth in all eight models (72 to 96 %; all p < 0.01), resulting in reduced tumor weight versus vehicle controls. Regorafenib reduced tumor angiogenesis 3- to 11-fold versus controls in all models (all p < 0.05), reduced tumor proliferation 2- to 5-fold in six of the eight models (all p < 0.05), and induced apoptosis in seven models. CONCLUSION: Regorafenib was effective in patient-derived models of gastric cancer of different histological subtypes, with inhibition of tumor growth, angiogenesis, and tumor-cell proliferation observed in almost all models. These findings are consistent with the observed activity of regorafenib in preclinical models of other gastrointestinal tumors, and support further clinical investigation in gastric cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13046-015-0243-5) contains supplementary material, which is available to authorized users.